2017
DOI: 10.1016/j.envint.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome is associated with exposure to organochlorine pesticides in Anniston, AL, United States

Abstract: The Anniston Community Health Survey, a cross-sectional study, was undertaken in 2005–2007 to study environmental exposure to polychlorinated biphenyl (PCB) and organochlorine (OC) pesticides and health outcomes among residents of Anniston, AL, United States. The examination of potential risks between these pollutants and metabolic syndrome, a cluster of cardiovascular risk factors (i.e., hypertension, central obesity, dyslipidemia and dysglycemia) was the focus of this analysis. Participants were 548 adults w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 62 publications
(93 reference statements)
3
37
0
Order By: Relevance
“…POP exposure may contribute to excess adiposity and other forms of metabolism dysfunction [31]. Organochlorine pesticide exposure was significantly associated with the risk of metabolic syndrome in the Anniston Health Study population, while no association was observed for PCBs [5]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…POP exposure may contribute to excess adiposity and other forms of metabolism dysfunction [31]. Organochlorine pesticide exposure was significantly associated with the risk of metabolic syndrome in the Anniston Health Study population, while no association was observed for PCBs [5]. …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the extensive use of pesticides globally has also triggered growing concerns regarding environmental impacts and adverse health effects [2,3,4]. Several organochlorine pesticides were associated with metabolic syndrome [5]. Approximately 105 pesticides have been identified as endocrine disruptors affecting the natural hormone balance in the human body [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies indicate exposure to certain organochlorine (OC) pesticides is positively associated with the development of insulin resistance, diabetes, and the metabolic syndrome . Animal studies have revealed that exposure to POPs in the presence of fatty fish oil led to the development of insulin resistance, abdominal obesity, and hepatosteatosis .…”
Section: Introductionmentioning
confidence: 99%
“…3 Epidemiological studies indicate exposure to certain organochlorine (OC) pesticides is positively associated with the development of insulin resistance, diabetes, and the metabolic syndrome. 4,5 Animal studies have revealed that exposure to POPs in the presence of fatty fish oil led to the development of insulin resistance, abdominal obesity, and hepatosteatosis. 6,7 The analysis of data from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2002 indicated that diabetic prevalence in individuals was strongly positively associated with concentrations of POPs serum concentrations, with OC pesticides being most strongly and consistently associated with the metabolic syndrome.…”
mentioning
confidence: 99%